O galope nordestino diante do parque industrial: o projeto estético do Quinteto Armorial no Brasil moderno - Santos, Nívea Lins [UNESP] (2015)
This research aims to understand what were the goals for the musical creation of the Armorial Quintet - which had its development during the 1970s and belonged to the Armorial Movement - both for aesthetic reasons and musical techniques, and in its historical aspects and social. This movement had the heart, in the musical context, the development of a national chamber music from the fusion of sounds spoken popular northeastern hinterland and canons of European high culture tradition. However, the urban-industrial modernization of the historical moment experienced by the movement and hence the Armorial Quintet, she was in a broad process of consolidation, enabling debates between various national projects in favor of what should be Brazilian culture: if integrated into modern logic and market and / or directed to return to our traditions. According to armorialistas, popular music aired by the major recording industries was essentially commercial and, therefore, should be questioned because they do not worry about the national authenticity. It is noteworthy that the unusual nature of the modern world established more dynamic relationships - and even contradictory - in Brazil; therefore, the relationship between tradition and modernity was discussion agenda for many artists and intellectuals, and the armorialistas some of them. According to the Armorial, especially in view of his mentor, Ariano Suassuna, some elements of modernity had the potential to jeopardize more traditional features in order to unconfigure our identity (whether it Northeastern or national) and not properly valuing our heritage / root. In that sense, we seek to understand how to built the musicality of the Armorial Quintet, which directed the development of a more artisanal sound material and very close to what had already defended Mario de Andrade